2020
DOI: 10.1080/23322969.2020.1806727
|View full text |Cite
|
Sign up to set email alerts
|

Refugees and equity policy in Australian higher education

Abstract: Measured in per capita terms, Australia has one of the most generous refugee resettlement programs in the world. This paper investigates the extent to which refugee status is recognized as a category of disadvantage in Australian higher education. Drawing on a scalar view of policy work and Fraser's notion of misframing, the paper assesses the policy visibility of humanitarian entrants. It compares sectoral equity provisions with national and institutional arrangements that target refugees. The findings reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Long-term social justice implications of the political rupture caused by populism and racial tensions (Castells, 2018) remain unknown and deserves a critical exploration. With the growing problem of economic, social, and racial inequality, education policy has also become a site of political struggle (Dorling, 2015;Molla, 2020;Reay, 2017). Moreover, climate change poses an existential threat.…”
Section: Emerging Empirical Contextsmentioning
confidence: 99%
“…Long-term social justice implications of the political rupture caused by populism and racial tensions (Castells, 2018) remain unknown and deserves a critical exploration. With the growing problem of economic, social, and racial inequality, education policy has also become a site of political struggle (Dorling, 2015;Molla, 2020;Reay, 2017). Moreover, climate change poses an existential threat.…”
Section: Emerging Empirical Contextsmentioning
confidence: 99%
“…While research has identified the resilience of students from a refugee background and noted the strengths of their ambitions when given opportunities, too often the experiences and needs of these students are homogenised as deficiencies in higher education (Morrice 2013 ; Naidoo et al 2018 ). University practices focus on student deficits rather than strengths, and they fail to recognise the value of refugees’ prior experiences (Molla 2020 ; Perry and Mallozzi 2011 ). Policy disconnects also occur when language preparation and educational support are provided at levels too low for integrating refugees into higher education (Lenette et al 2019 ; Streitwieser et al 2017 ).…”
Section: Literature Review: Refugees and Higher Educationmentioning
confidence: 99%
“…Since their legal status and membership of a place is uncertain; even those who do well in the school system in Australia and are selected for entry into the university system often decline the places they are offered because they cannot afford to enrol as an international student (Hirsch and Maylea 2016 ). Moreover, whilst Australia has a relatively generous refugee settlement programme, there is a mismatch between the multicultural initiatives at federal and state level and the relative invisibility of federal and state policies to promote multiculturalism at the sectoral level of higher education (Molla 2020 ). Many universities find that government policies that treat students from refugee and asylum-seeking backgrounds as high-fee-paying international students restrict their institutional ability to implement multicultural policies.…”
Section: Literature Review: Refugees and Higher Educationmentioning
confidence: 99%
See 2 more Smart Citations